The Determination of Volcanic Characteristics Based on Deuterium and Oxygen-18 Isotope Compositions: A Case Study at Dieng Plateau, Central Java - Priatna Priatna; Nana Sulaksana; Johanes Hutabarat; Iyan Haryanto (Indonesian Journal on Geoscience, 2020)
DOI:10.17014/ijog.7.2.201-213To find out volcanic characteristics, a geochemical approach can be used, one of which is through the measurement of deuterium and oxygen-18 isotopes from condensate and crater water samples. In this study, Dieng Plateau in Central Java was chosen, because it has a wide spread of fumarole fields and crater water. In addition, research in the Dieng Plateau is very useful in the management of geological-based tourism and geopark development in the future. Results of isotope analysis in Candradimuka Crater show the average number of isotope deuterium is δD – 500/00 and isotope oxygen-18 is δ18O –30/00 which produce the value of the mixing fraction of f 18O = 47.11%. This figure is the highest isotope number compared to other craters on the Dieng Plateau. The high value of the isotope-18 mixing fraction is supported by a strong plume from three vents in Candradimuka. Meanwhile, the results of crater water isotope tests obtained the highest results in Sikidang Crater with the value of the deuterium isotope is δD = – 10.300/00 and the isotope oxygen-18 is δ18O = 6.570/00 which are in the metamorphic water area from the mixing of magmatic processes with surface meteoric water. Based on the deuterium isotope approach with oxygen-18 crater water and fumarole condensate supported by subsurface temperature data, most of the Dieng Plateau has magmatic-hydrothermal characteristics, except Candradimuka Crater which belongs to the magmatic group.